1998
DOI: 10.1021/la971339a
|View full text |Cite
|
Sign up to set email alerts
|

Photophysical and Solution Properties of Naphthalene-Labeled Styrene/N,N-Dimethyl Maleimido Propylammonium Propane Sulfonate Copolymer

Abstract: The photophysical and solution properties of naphthalene-labeled styrene/N,N-dimethyl maleimido propylammonium propane sulfonate copolymer, poly(SDMPAPS)/NA, were studied in terms of fluorescence, cloud point, and viscosity measurements. The ratio of intensities of the excimer and monomer fluorescence (I E/I M) was shown as a function of polymer concentration in deionized water. The value of I E/I M decreases with an increase in the salt concentration. The addition of anionic surfactants to the aqueous solutio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 33 publications
1
37
0
Order By: Relevance
“…[24] Previous reports also have thoroughly examined the difference in dilute aqueous solution properties such as viscosity, hydrodynamic diameter, cloud point, and the degree of binding. [25][26][27][28][29][30][31] These properties provide a reasonable assessment of the macroscopic behavior, however, a detailed analysis using a more sensitive characterization method is required. When naphthalene labels were incorporated into the water-soluble polymer, photophysical properties and the behavior of polymers in aqueous solution could be clearly defined.…”
Section: Introductionmentioning
confidence: 99%
“…[24] Previous reports also have thoroughly examined the difference in dilute aqueous solution properties such as viscosity, hydrodynamic diameter, cloud point, and the degree of binding. [25][26][27][28][29][30][31] These properties provide a reasonable assessment of the macroscopic behavior, however, a detailed analysis using a more sensitive characterization method is required. When naphthalene labels were incorporated into the water-soluble polymer, photophysical properties and the behavior of polymers in aqueous solution could be clearly defined.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Fig. 1 shows low intrinsic viscosities of the zwitterionic poly(DEMAPhAPS) solution with low NaCl concentration resulting from the inter-and intra-associations of the polymer chains 37,40) . As the concentration of the salt was increased, the associations began to drop and the intrinsic viscosity began to increase.…”
Section: Solution Property Of Cationic Poly(demmaphams) and Zwitteriomentioning
confidence: 99%
“…Several authors have observed that higher salt concentration leads to lower inter-and intra-associations of polybetaines and, subsequently, to higher intrinsic viscosity 30,37,38,40) . Results obtained from the intrinsic viscosity for cationic poly(DEMMAPhAMS) are the opposite to those for zwitterionic poly(DEMAPhAPS).…”
Section: Solution Property Of Cationic Poly(demmaphams) and Zwitteriomentioning
confidence: 99%
See 1 more Smart Citation
“…For the design of new medical applications, the selection of materials should be carefully considered. Several reports for the design, synthesis, and preparation of new functional materials were studied to find suitable materials for biomedical applications such as polyacrylate, polyester, polyamide, polyimide, polyester, polynorborene, polytetrafluoroethylene, polydiphenylacetylenes, and polymeric resins [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. Also, surface modification technology was considered to change the surface microenvironment of the materials [17,18].…”
Section: Introductionmentioning
confidence: 99%